Tool for cost-benefit analysis of mitigation option in rice production - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Rice-CBA tool was developed using the participatory approach to ensure relevance in the context of rice development in Vietnam. It has been validated by the national partners/stakeholders, introduced to various user groups, and finetuned based on the feedback. It is now available for uptake on the GHG Mitigation homepage.